A NEW SPECIES OF CARDIOMYINAE (RODENTIA, HYDROCHOERIDAE) FROM WESTERN ARGENTINA. ITS AGE AND CONSIDERATIONS ON ONTOGENY AND DIVERSITY OF THE SUBFAMILY (Ameghiniana, 2012)
A new Cardiomyinae rodent (Hydrochoeridae) from Arroyo Seco de la Frazada, Mendoza Province, Argentina, is described. The new species, Caviodon cuyano sp. nov., is distinguished by its greater robustness, deeper fissures, and greater number of prisms in M3, which are derived characters within the context of Hydrochoeridae evolution. An assessment of the species of Caviodon Ameghino showed that tooth growth is allometric and occlusal morphology becomes more complex during ontogeny, as in hydrochoerines. The true diversity of this genus, when tooth postnatal ontogeny is considered, may be less than heretofore estimated. The fossil-bearing levels, the middle section of the Aisol Formation, have been considered no older than Huayquerian in age (late Miocene). The evolutionary stage of the new species suggests that the age of these sediments could be even younger, no older than early Pliocene and possibly up to late Pliocene.Resumen. UNA NUEVA ESPECIE DE CARDIOMYINAE (RODENTIA, HYDROCHOERIDAE) DEL OESTE DE ARGENTINA. SU EDAD Y CONSIDERACIONES SOBRE ONTOGENIA Y DIVERSIDAD DE LA SUBFAMILIA. Se describe un nuevo roedor Cardiomyinae (Hydrochoeridae) proveniente de Arroyo Seco de la Frazada, provincia de Mendoza, Argentina. La nueva especie, Caviodon cuyano sp. nov., se distingue por su mayor robustez, mayor profundidad de las hendiduras y mayor número de prismas en el M3, caracteres considerados derivados en el contexto de la evolución de la Familia Hydrochoeridae. Una evaluación de las especies de Caviodon Ameghino permitió constatar que los dientes crecen alométricamente y la morfología oclusal se hace más compleja durante la ontogenia, como en los hidroquerinos. La diversidad de este género podría ser menor que la estimada hasta ahora, cuando se tiene en cuenta la ontogenia dentaria postnatal. Los niveles portadores, sección media de la Formación Aisol, fueron considerados no más antiguos que huayquerienses (Mioceno tardío). El estado evolutivo de la nueva especie sugiere que la edad de los sedimentos portadores podría ser más reciente, correspondiente al Plioceno temprano o incluso al Plioceno tardío.